Effect of Target properties on the Plasma Characteristics that produced by Laser at Atmospheric Pressure - Abbas, Qusay Adnan (Iraqi Journal of Science, 2019)
In this paper, Al and Cu Plasmas that produced by pulsed Nd:YAG laser with fundamental wave length with a pulse duration of 6 nS focused onto Al and Cu targets in atmospheric air are investigated spectroscopically. The influence of pulse laser energy on the some Al and Cu plasmas characteristics was diagnosed by using optical emission spectroscopy for the wavelength range 320-740 nm. The results observed that the increase of pulse laser energy causes to increase all plasma characteristics of both plasmas under study and shown increasing of the emission line intensity. The appearance of the atomic and ionic emission lines of an element in the emission spectrum depends on the ionization energy of target atoms. The plasma characteristics are subjected to the ionization energy of the target element and laser energy.